Sulfur Cycling and Mass Balance at Meridiani, Mars. Issue 21 (3rd November 2019) - Hynek, Brian M.; McCollom, Thomas M.; Szynkiewicz, Anna
Abstract: The Opportunity rover was sent to Meridiani Planum, Mars, to investigate aqueous processes as inferred from orbiter observations of hematite. While the rover found the source of the hematite signal, it also identified abundant bedrock enriched in SO3 on average by >20 wt% throughout its >40‐km traverse. Geological mapping and orbiter data show that the layered sulfate deposits occur over ~4 × 10 5 km 2, an area larger than Germany. Multiple scenarios for formation of the sediment and sulfur sources in the Meridiani sulfate‐rich bedrock have been proposed, including groundwater upwelling in a playa environment, volcanic ash, ice deposits, and fluvial input. Mass balance calculations show that none of the existing scenarios as currently portrayed can account for the total sediment volume and sulfur mass in the Meridiani region. Thus, after 14 Earth years of rover observations, there are still fundamental questions that remain regarding formation mechanisms of the sulfate‐rich bedrock. Plain Language Summary: Sedimentary rocks highly enriched in sulfur were investigated by the Opportunity rover at Meridiani Planum, Mars. These materials extend over a broad region. Mass balance calculations were completed to assess whether or not the proposed scenarios for Meridiani sulfur and sediments could be reconciled with observations. We find that none of the previously proposed scenarios for the Meridiani region can account for the volume of sediment and mass of sulfur in that area. Thus, new scenarios of sediment and sulfate transport are required to reconcile the sediment volume and chemistry determined from landed and orbiter observations. Key Points: The Meridiani region, Mars, is one of the most sulfate‐rich places known, and was studied by the Opportunity rover for over 14 Earth years Ground truth provides a sulfur content that is ~20 wt% in the bedrock examined by Opportunity Broader geologic mapping implies a total sulfur and sediment abundance that is incompatible with all proposed formation scenarios